Personen v.l.n.r. bovenste afb.: Wilhelm II, Hindenburg. Daaronder v.l.n.r.: Hindenburg, von Papen - Holtz, Karl
Personen v.l.n.r. bovenste afb.: Wilhelm II, Hindenburg. Daaronder v.l.n.r.: Hindenburg, von Papen.